Growth modification of seeded calcite using carboxylic acids: Atomistic simulations - Aschauer, U.; Spagnoli, Dino; Bowen, P.; Parker, S. (Elsevier, 2010)
Molecular dynamics simulations were used to investigate possible explanations for experimentallyobserved differences in the growth modification of calcite particles by two organic additives, polyacrylicacid (PAA) and polyaspartic acid (p-ASP). The more rigid backbone of p-ASP was found to inhibit the formationof stable complexes with counter-ions in solution, resulting in a higher availability of p-ASP comparedto PAA for surface adsorption. Furthermore the presence of nitrogen on the p-ASP backbone yieldsfavorable electrostatic interactions with the surface, resulting in negative adsorption energies, in anupright (brush conformation). This leads to a more rapid binding and longer residence times at calcitesurfaces compared to PAA, which adsorbed in a flat (pancake) configuration with positive adsorptionenergies. The PAA adsorption occurring despite this positive energy difference can be attributed to thedisruption of the ordered water layer seen in the simulations and hence a significant entropic contribution to the adsorption free energy. These findings help explain the stronger inhibiting effect on calcite growth observed by p-ASP compared to PAA and can be used as guidelines in the design of additives leading to even more marked growth modifying effects.